MAN-MADE JUMPS IN TERRAIN-PARKS AND THE RISK OF SEVERE SKI-PATROL REPORTED INJURIES IN ALPINE SKIERS AND SNOWBOARDERS. Issue 4 (1st February 2017) - Goulet, Claude; Hamel, Denis; Tremblay, Benoit; Audet, Olivier; Hagel, Brent E.
Abstract : Background: Two ski areas in Québec, Canada, removed man-made jumps from their terrain parks (TPs) from seasons 2007–08 to 2009–10. Jumps were reintroduced starting in season 2010–11. Objective: To determine if man-made jumps in TPs are associated with severe alpine ski and snowboard injuries. Design: Retrospective study using ski-patrol Injury Report Forms (IRFs). Setting: All ski areas with a TP in Québec. Patients (or Participants): Skiers and snowboarders who reported to the ski patrol with a TP injury during seasons 2000–01 to 2014–15, at all Québec ski areas with TP (two where jumps were removed, and others without jump removal). Interventions (or Assessment of Risk Factors): Risk factor data and injury outcomes were collected through IRFs. Main Outcome Measurements: Severe injuries were defined based on type of injury or ambulance evacuation. The proportions of severe injuries before jump removal (2000–01 to 2006–07) and during jump reintroduction (2010–11 to 2014–15) were compared with proportions during jump removal (2007–08 to 2009–10). Logistic regression analysis was used to adjust the comparisons for age, sex, skill level, helmet use, and type of activity. Generalized Estimating Equations were used to account for potential ski area clustering of outcomes. Results: At the hills that removed jumps (4, 006 IRFs analysed), the crude proportion of severe TP injuries was 19.3% before removal, 14.5% during removal, and 24.3% at reintroduction. The odds of severe injury were higher before removal (adjusted odds ratio [AOR]: 1.39; 95% CI: 1.03–1.87) and during reintroduction (AOR: 1.90; 95% CI: 1.52–2.37). At other hills over the same time period (21, 449 IRFs), there was no change before (23.7%) and during (22.0%) jump removal (AOR: 1.07; 95% CI: 0.94–1.21), but the proportion of severe injuries increased after reintroduction (26.4%; AOR: 1.26; 95% CI: 1.10–1.43). Conclusions: Results suggest that removing man-made jumps from TPs may prevent severe injuries.